Neurological software tool for reliable atrophy measurement (NeuroSTREAM) of the lateral ventricles on clinical-quality T2-FLAIR MRI scans in multiple sclerosis - Dwyer, Michael G; Silva, Diego; Bergsland, Niels; Horakova, Dana; Ramasamy, Deepa; Durfee, Jaqueline; Vaneckova, Manuela; Havrdova, Eva; Zivadinov, Robert (NeuroImage. Clinical, 2017)
BACKGROUND: There is a need for a brain volume measure applicable to the clinical routine scans. Nearly every multiple sclerosis (MS) protocol includes low-resolution 2D T2-FLAIR imaging. OBJECTIVES: To develop and validate cross-sectional and longitudinal brain atrophy measures on clinical-quality T2-FLAIR images in MS patients. METHODS: A real-world dataset from 109 MS patients from 62 MRI scanners was used to develop a lateral ventricular volume (LVV) algorithm with a longitudinal Jacobian-based extension, called NeuroSTREAM. Gold-standard LVV was calculated on high-resolution T1 1 mm, while NeuroSTREAM LVV was obtained on low-resolution T2-FLAIR 3 mm thick images. Scan-rescan reliability was assessed in 5 subjects. The variability of LVV measurement at different field strengths was tested in 76 healthy controls and 125 MS patients who obtained both 1.5T and 3T scans in 72 hours. Clinical validation of algorithm was performed in 176 MS patients who obtained serial yearly MRI 1.5T scans for 10 years. RESULTS: Correlation between gold-standard high-resolution T1 LVV and low-resolution T2-FLAIR LVV was r = 0.99, p < 0.001 and the scan-rescan coefficient of variation was 0.84%. Correlation between low-resolution T2-FLAIR LVV on 1.5T and 3T was r = 0.99, p < 0.001 and the scan-rescan coefficient of variation was 2.69% cross-sectionally and 2.08% via Jacobian integration. NeuroSTREAM showed comparable effect size (d = 0.39-0.71) in separating MS patients with and without confirmed disability progression, compared to SIENA and VIENA. CONCLUSIONS: Brain atrophy measurement on clinical quality T2-FLAIR scans is feasible, accurate, reliable, and relates to clinical outcomes.
Keywords: Multiple sclerosis; Cross-Sectional Studies; Male; Automated measurement; magnetická rezonanční tomografie; Multiple Sclerosis; atrofie; Adult; dospělí; mužské pohlaví; lidé středního věku; Software; Brain atrophy; reprodukovatelnost výsledků; Reproducibility of Results; Ventricular volume; Atrophy; lidé; ženské pohlaví; Humans; ventriculi laterales; průřezové studie; Radionuclide Imaging; software; Magnetic Resonance Imaging; Female; radioisotopová scintigrafie; roztroušená skleróza; Lateral Ventricles; Middle Aged